2017
DOI: 10.1007/s11999-017-5342-5
|View full text |Cite
|
Sign up to set email alerts
|

Does the FIFA 11+ Injury Prevention Program Reduce the Incidence of ACL Injury in Male Soccer Players?

Abstract: Level I, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
122
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 48 publications
3
122
1
8
Order By: Relevance
“…Furthermore, it is noteworthy that 6 of the 8 ACLR in the Standard‐11+ group were non‐contact injuries, while all ACLR in the P2 post group involved contact with another player. Previous 11+ research found a similar dose‐related effect to ACLR incidence, and our findings present encouraging data that may help reduce non‐contact ACLR in sub‐elite football.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, it is noteworthy that 6 of the 8 ACLR in the Standard‐11+ group were non‐contact injuries, while all ACLR in the P2 post group involved contact with another player. Previous 11+ research found a similar dose‐related effect to ACLR incidence, and our findings present encouraging data that may help reduce non‐contact ACLR in sub‐elite football.…”
Section: Discussionsupporting
confidence: 85%
“…The program is effective in reducing lower extremity injuries in collegiate age men and high school age women. 1,2,5 The 11+ program focuses on proper lower extremity alignment and landing technique with emphasis on avoiding valgus movement patterns (knee abduction, hip adduction, and hip internal rotation). This study found both the 11+ and Control groups had bilateral increases in peak knee abduction angle, coupled with unilateral increases in hip abduction and external rotation on the non-dominant side for the 11+ group and dominant for the Control group.…”
Section: Discussionmentioning
confidence: 99%
“…5 High school age women soccer players also seemed to benefit from the program demonstrating a 32% reduction in lower extremity injury risk, and although not statistically significant a 38% reduction in knee injury risk. 2 The efficacy of the 11+ has not been tested in collegiate women soccer players, however they are at a known high risk for ACL injuries.…”
Section: Introductionmentioning
confidence: 92%
“…Another more recent study has been conducted in male athletes. 43 In this study, a large number of soccer players (675 intervention, 850 control) participated in an ACL injury prevention training program and a 77% reduction in the risk of ACL injury was found. This is an encouraging finding and indicates that the effectiveness of ACL injury prevention training programs in males should be further investigated to confirm the above results, which are based on limited data.…”
mentioning
confidence: 87%